Design and control of electric bus vehicle model for estimation of energy consumption. Issue 24 (2019) - Czogalla, Olaf; Jumar, Ulrich
Abstract: Public transport fleet operators are interested in lowering emissions due to tightened standards for city air quality. However, stakeholders in the electrification process with battery electric buses (BEB) are exposed to a complex network of dependencies from governmental, economic, transport, and energy domains. Particularly, specialized tools for planning routes, vehicles, and charging infrastructure are missing at municipal-operational level of BEB deployment. Aim of the project as core of this paper is to develop methods and tools to support planning aspects of bus fleet electrification. Planners should be enabled to decide about the feasibility of deploying BEB on selected routes within the public transportation network by using input data of network design, schedule, vehicle characteristics, and charging infrastructure. Using the developed vehicle simulation model of BEBs, it is possible to scale battery capacities for full day duty-cycles on real bus routes under consideration of terrain grades, realistic traffic conditions, and opportunity charging.